The Effect of Gibberellic Acid and Diammonum Phosphate (DAP) Fertilizer on Some Physiological Characteristices of Lentil’s (Lens Culinaris Mediic) Roots. - Jaleel, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A biological experiment was done in the green house of Biology Department, college of Education (Ibn – AL haitham), Baghdad university, in pots (2Kg size), for growth season 2009, to study the effect of two concentrations of gibberellic acid which was (50) and (100) ppm, and two levels of Diamonium phosphate fertilizer which was(0.16) and (0.32) gm/2kg pot which equal (40) and (80) kg/d, in growth of root of one lentil cultivar (AL- Baraka), upon compeletely randomized design with three replications. The results showed that there was a significant increase in (root’s length, volumes of roots, fresh and dry weights, number of nodules, and the percents of nitrogen and protein), by increasing of gibberellic acid concentrations, and by increasing of fertilizer’s levels, comparing with controls. The influence of interaction between gibberellic acid and fertilizer showed a siginficant increase in characteristices were studied. The levels of (80) kg DAP/d with (50) ppm of GA3, (40)kg DAP/d with (100) ppm of GA3, and (80)kg DAP/d with (100) ppm of GA3 showed the best significant increase in characteristics were studied. The level of (80)Kg DAP/d. with (100) ppm of GA3 showed the best significant results comparing to other interaction treatments.